2006
DOI: 10.1038/nature04861
|View full text |Cite
|
Sign up to set email alerts
|

Noise-resistant and synchronized oscillation of the segmentation clock

Abstract: Periodic somite segmentation in vertebrate embryos is controlled by the 'segmentation clock', which consists of numerous cellular oscillators. Although the properties of a single oscillator, driven by a hairy negative-feedback loop, have been investigated, the system-level properties of the segmentation clock remain largely unknown. To explore these characteristics, we have examined the response of a normally oscillating clock in zebrafish to experimental stimuli using in vivo mosaic experiments and mathematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
281
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(297 citation statements)
references
References 42 publications
16
281
0
Order By: Relevance
“…If so, the order parameter could be measured by relating the activity of the reporter to a nominally defined 'phase' and using (2) to measure global synchrony. The effects of perturbations to global synchrony, such as the qualitative experiments performed by Horikawa et al [3], could then be measured experimentally and the resulting order parameter data could be directly compared with theoretical models, such as (1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…If so, the order parameter could be measured by relating the activity of the reporter to a nominally defined 'phase' and using (2) to measure global synchrony. The effects of perturbations to global synchrony, such as the qualitative experiments performed by Horikawa et al [3], could then be measured experimentally and the resulting order parameter data could be directly compared with theoretical models, such as (1).…”
Section: Resultsmentioning
confidence: 99%
“…Using zebrafish, Horikawa et al [3] observed that cells which were either in, or had just recently exited, M phase of the cell cycle tended to be out of phase with neighbouring oscillators in the posterior PSM. They concluded that during M phase of the cell cycle the transcription necessary to progress the somitogenesis clock was paused as the cells prepared for division, thus dividing cells drifted out of phase with their neighbours.…”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Horikawa and colleagues investigated the coupling of segmentation clocks within individual PSM cells by means of Notch-dependent intercellular communication regulated by the internal hairy oscillator. They showed, using a combination of experimental methods and modeling, that this could lead to synchronized oscillations robust to the presence of noise (Horikawa et al, 2006).…”
Section: Clock and Induction Modelmentioning
confidence: 99%